2021
DOI: 10.3390/educsci11080437
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Video-Based Learning Using Tablet Computers to Teach Job Skills to Students with Intellectual Disabilities

Abstract: Information and Communication Technologies (ICT) provide different opportunities to students with intellectual disabilities and to professionals who work with them. However, few studies address the use of collaborative learning platforms and handheld devices to enhance the integration of people with intellectual disabilities in the labour market. We present a learning experience where active methodologies, such as collaborative work, are combined with the use of iPads and a learning management system following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Collaborative learning in STEM education encourages students to communicate and increase their satisfaction in teaching and learning activities [88]. It allows them to talk, discuss, and convey their ideas in groups.…”
Section: Discussionmentioning
confidence: 99%
“…Collaborative learning in STEM education encourages students to communicate and increase their satisfaction in teaching and learning activities [88]. It allows them to talk, discuss, and convey their ideas in groups.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of digital learning materials, tablets have the potential to enhance learning activities. Furthermore, they could increase student motivation [25], help teachers improve student learning outcomes, and support learning outside the classroom. This implies that tablet computers have a great potential impact when used properly by university students for learning purposes, especially as technology is increasingly easy to master and use.…”
Section: Theoretical Background 21 Tablet Computers In Educationmentioning
confidence: 99%
“…Many previous studies examined university students' attitudes towards the use of tablet computers for learning purposes but only analyzed one element in the education system [25,[32][33][34]. Haßler, Major, & Hennessy [3] reviewed the use of tablets for learning purposes and found that the effect size of tablet computer use in schools was not as expected.…”
Section: Theoretical Background 21 Tablet Computers In Educationmentioning
confidence: 99%
“…In the workplace, task analysis can be used to provide visual prompts of the steps needed to perform any job duty in a variety of settings (e.g., restaurants, office, hotel, and retail). For example, task analyses using video modeling have been used successfully to teach students with ID job skills (Randall, Johnson, Adams, Kiss, & Ryan, 2020; Roldán-Álvarez, Martín, & Haya, 2021). The students were taught how to record videos using an iPad, and then recorded and uploaded a video about an assigned job scenario.…”
Section: Task Analysis Appsmentioning
confidence: 99%